2021
DOI: 10.1177/01461672211048110
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in Facial Trustworthiness Impressions: Kernel of Truth or Modern Physiognomy? A Meta-Analysis

Abstract: Being able to identify trustworthy strangers is a critical social skill. However, whether such impressions are accurate is debatable. Critically, the field currently lacks a quantitative summary of the evidence. To address this gap, we conducted two meta-analyses. We tested whether there is a correlation between perceived and actual trustworthiness across faces, and whether perceivers show above-chance accuracy at assessing trustworthiness. Both meta-analyses revealed significant, modest accuracy (face level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Given that facial impressions have reasonably low validity (in the sense that a given individual who looks trustworthy may not be trustworthy, Foo et al, 2021), why do we persist in forming and acting on them 2020), Nature Human Behaviour so readily? Theories of first impressions suggest the reason is that impression formation is nonetheless functional; we form impressions because we seek to predict our social interactions (Fiske et al, 2007;Oosterhof & Todorov, 2008;Sutherland et al, 2018;Zebrowitz, 2005).…”
Section: Why Do We Form Face Impressions?mentioning
confidence: 99%
See 4 more Smart Citations
“…Given that facial impressions have reasonably low validity (in the sense that a given individual who looks trustworthy may not be trustworthy, Foo et al, 2021), why do we persist in forming and acting on them 2020), Nature Human Behaviour so readily? Theories of first impressions suggest the reason is that impression formation is nonetheless functional; we form impressions because we seek to predict our social interactions (Fiske et al, 2007;Oosterhof & Todorov, 2008;Sutherland et al, 2018;Zebrowitz, 2005).…”
Section: Why Do We Form Face Impressions?mentioning
confidence: 99%
“…Many studies have shown that people tend to agree on their impressions and that impressions from faces are formed readily (Klapper et al, 2016; Oosterhof & Todorov, 2008), implicitly (Swe et al, 2020) and with minimal information; even a single glimpse of a photograph can suffice (Willis & Todorov, 2006). Impressions of traits from faces have at best only limited accuracy, meaning that their everyday use is problematic (Foo et al, 2021). Yet, despite this limited accuracy, facial impressions often have critical social consequences.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations